2006
DOI: 10.1108/13612020610702009
|View full text |Cite
|
Sign up to set email alerts
|

Competitive e‐tailing strategies for fair trade organizations

Abstract: PurposeThis study aims to provide competitive e‐tailing strategies for fair trade organizations using a benchmarking approach.Design/methodology/approachA coding guide was developed to obtain information available on 28 fair trade web sites and 28 commercial web sites focusing on company information, product information, distribution channels, customer service, and web site structure/media service.FindingsResults revealed several evidences that fair trade organizations presented limited information online, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This is supported by Joergens's (2006) research into ethical fashion, which found that focus group participants aged between 21 and 25 were ''positively surprised'' by the styles of the garments in the People Tree catalogue. Halepete and Park (2006) found that Fair Trade retailers provided less information to consumers than successful commercial competitors. In contrast to this, People Tree provides information to its customers relating to its products and suppliers, which currently exceeds the amount of information provided by its mainstream retail competitors in this respect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is supported by Joergens's (2006) research into ethical fashion, which found that focus group participants aged between 21 and 25 were ''positively surprised'' by the styles of the garments in the People Tree catalogue. Halepete and Park (2006) found that Fair Trade retailers provided less information to consumers than successful commercial competitors. In contrast to this, People Tree provides information to its customers relating to its products and suppliers, which currently exceeds the amount of information provided by its mainstream retail competitors in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…(p. 418). Halepete and Park (2006) claim that there is ''a growing awareness of Fair Trade and socially responsible businesses among consumers and industry professionals'' (p. 492). This view was validated by an increase of 46 per cent in the sales of Fair Trade products in general in the UK in 2006 (Santi and Spear, 2007).…”
Section: Marketing Fair Trade Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suggested strategies were increasing flexibility in the supply of artisans; recruiting volunteers for sales and retailing in the US; increasing quality and ethnicity in product design; linking customer to artisans; and creating new store images. Website designs between FTOs and mainstream retailers were also compared to encourage competitive approaches of marketing (see Halepete & Park, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…With the fast growing consumer awareness, fair trade apparel has been a target for research in the areas of retail performance (Halepete & Park, 2006;Littrell & Dickson, 1998), corporate commitment (Goworek, 2011;Jones, Hillier, & Comfort, 2014), consumer characteristics (Halepete, Littrell, & Park, 2009), and purchase behaviors (Ma & Lee, 2012). While fair trade movement of apparel products is rapidly expanding, there is a dearth of understanding about the characteristics of consumers who regularly purchase fair trade apparel products.…”
Section: Introductionmentioning
confidence: 99%